A comprehensive approach to assessing eutrophication for the Guangdong coastal waters in China - Zhou, Jing; Wang, You-Shao (Frontiers in Marine Science, 2024)
Eutrophication is a global issue associated with increasing anthropogenic activities. Previous studies have mainly focused on nutrients and phytoplankton biomass in some typical estuaries and bays along the Guangdong coast, while integrated evaluations of eutrophication status based on ecological symptoms is still rare in this area. To better understand the health of the Guangdong coastal waters, two comprehensive methods including the Assessment of Estuarine Trophic Status (ASSETS) and the Northwest Pacific Action Plan Common Procedure (NOWPAP CP) were employed with slight modifications. The study area was divided into eight coastal zones (Z1~Z8) based on multiple criteria including salinity, catchment range, and administrative division. The results of the modified NOWPAP CP method demonstrated a generally increasing trend in the degree and effects of nutrient enrichment along the Guangdong coast in the past 30 years mainly due to the increasing nutrients and chlorophyll a (Chl-a). The results of the modified ASSETS method revealed that the water quality was between moderate and high for most coastal zones during 2015-2018, with the highest score (0.83) in the northern part of the Pearl River Estuary (PRE). However, the ecological symptoms showed inconsistent spatial patterns with the water quality, being high or moderate high in Z2 (including Zhanjiang Harbor and Leizhou Bay), Z4~Z5 (representing the northern and southern parts of the PRE, respectively), and Z6 (containing Mirs Bay and Daya Bay) for severe ecological symptoms, such as high levels of Chl-a, frequent harmful algal blooms (HABs). Moreover, eutrophication in Z4~Z6 may further deteriorate due to the increasing nutrient loads driven by growing economy and population. Synthetically, Z2, Z4~Z6 were graded between poor and bad for the overall eutrophication conditions (OEC), while Z1 (including the western and southern parts of the Leizhou Peninsula) and Z7 (consisting of Honghai Bay and Jieshi Bay) had a good OEC. The application of the modified ASSETS method effectively identified areas of severe eutrophication problems and the prospect of nutrient load along the Guangdong coast. The assessment results revealed the spatiotemporal variations and potential trends in the eutrophication status, providing scientific basis for the coastal management related to nutrient problems.